Wood products exposed outdoor could be weathered, especially in the tropical region with high in sun light intensity, rain intensity, and relative humidity. An effort that could be done to protect and enhance wood performance is finishing. The purpose of this research is to understand the durability of finishing layer of the finished wood exposed outdoor. The effects of surface condition of boards (planed and unplaned), sawing pattern (quarter sawn and plain sawn), and type of wood finishes (Ult - Wayan DARMAWAN; Itan Iskova PURBA (Departemen Hasil Hutan, IPB, 2009)
Wood products exposed outdoor could be weathered, especially in the tropical region with high in sun light intensity, rain intensity, and relative humidity. An effort that could be done to protect and enhance wood performance is finishing. The purpose of this research is to understand the durability of finishing layer of the finished wood exposed outdoor. The effects of surface condition of boards (planed and unplaned), sawing pattern (quarter sawn and plain sawn), and type of wood finishes (Ultran Lasur UV and Ultran Politur P-03 UV) were studied. The experimental results showed that finishing layer of Meranti batu was the lowest in durability. The results also indicated that durability of finishing layer depicted by unplanned and plain sawn boards were lower than that of the planed and quarter sawn board. The finishing layer was considered to provide a good protection to the surfaces of board against failures. The presence of failure due to microbial disfigurement and cracking on the surfaces of the finished samples (in average) were 15% and 18% consecutively. On the other hand, the percentages of failure were observed to be 95% due to microbial disfigurement and 81% due to cracking for the unfinished wood. Comparing the two exterior wood finishes used in this experiment, it was found that Ultran Politur P-03 UV provided almost the same protection against microbial disfigurement and cracking compared to Ultran Lasur UV. Keywords : Exterior finishing layer, microbe stain, surface crack, surface check